2007
DOI: 10.1111/j.1574-695x.2006.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose of Concanavalin-A enhances innate immune response and prevents liver injury in mice infected withCandida albicans

Abstract: The mechanisms through which Candida albicans is recognized by immune cells and how it triggers host defence are not completely understood. In this study, we evaluated the effect of Concanavalin-A on the clearance of C. albicans by infected mice and their production of proinflammatory cytokine tumor necrosis factor-alpha (TNF-alpha). Subgroups of 5 animals were pretreated with Con-A (250 mug mL(-1) PBS) and after 96 h were infected intraperitoneally with 10(7) cells of C. albicans CR15 (an isolate from a HIV+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 24 publications
3
15
0
2
Order By: Relevance
“…Dysfunction in cell-mediated immunity by low IFN-γ production has been also verified in patients with mucocutaneous candidiasis [7]. Therefore, strategies that cause an increase in Th1 immune response and increased phagocytic functions have been used in experimental models [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…Dysfunction in cell-mediated immunity by low IFN-γ production has been also verified in patients with mucocutaneous candidiasis [7]. Therefore, strategies that cause an increase in Th1 immune response and increased phagocytic functions have been used in experimental models [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…Previously, our group observed that containment of dimorphism was correlated with an increase in TNF-α levels, as described for concanavalin-A-activated macrophages in phagocytic assays [12]. TNF-α is a cytokine produced by macrophages that increases respiratory burst and antifungal activities [4,10,12,24,25,28].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, treatment with cytokines that present immunoregulatory activity has been studied, particularly those that promote the activation of neutrophils and macrophages. Studies involving experimental animal models have shown that Th1 cells play an important role in regulating the immune response to Candida albicans infection by secreting cytokines that modulate the activity of immune effector cells [3][4][5][6]. Cytokines produced by Th1 cells activate phagocytes to the fungicidal state, whereas those produced by Th2 cells exacerbate the disease, because they deactivate fungicidal effector cells [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As células do padrão T helper 1 (TH1), T helper 2 (TH2), T helper 17 (TH17) e T regulatórias (Tregs) com funções efetoras diferentes estão relacionadas com manifestações clínicas de diferentes graus de severidade ou superação da infecção ou ainda comensalismo (ROMANI; KAUFMANN, 1998;ROMANI, 2004;KOGUCHI;KAWAKAMI, 2002;HUFFNAGLE;DEEPE, 2003;CONCHON-COSTA et al, 2007;GAZIRI, 2008;FELIPE et al, 2008).…”
Section: Resposta Imune à Candida Albicansunclassified
“…Tais polissacarídeos e glicoconjugados são reconhecidos por várias lectinas que podem atuar independentemente ou em associação com receptores tipo Toll ou ainda com outros receptores de sinalização (CONCHON-COSTA et al, 2006;GAZIRI, 2008). Os receptores dectina-1 podem reconhecer o ligante independente ou associado a receptores tipo Toll-2 para conferir responsividade a β-glucanas microbianas GANTNER;SIMMONS;UNDERHILL, 2005;LOYOLA et al, 2007;ROSAS et al, 2008).…”
Section: O Sistema De Reconhecimento De Padrões Moleculares Associadounclassified